2002
DOI: 10.1113/jphysiol.2002.028183
|View full text |Cite
|
Sign up to set email alerts
|

Rapid non‐genomic inhibition of ATP‐induced Cl secretion by dexamethasone in human bronchial epithelium

Abstract: A non‐genomic antisecretory role for dexamethasone at low concentrations (0.1 nm to1 μm) is described in monolayers of human bronchial epithelial cells in primary culture and in a continuous cell line (16HBE14o‐ cells). Dexamethasone produced a rapid decrease of [Ca2+]i (measured with fura‐2 spectrofluorescence) to a new steady‐state concentration. After 15 min exposure to dexamethasone (1 nm), [Ca2+]i was reduced by 32 ± 11 nm (n= 7, P < 0.0001) from a basal value of 213 ± 36 nm (n= 7). We have shown previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 44 publications
3
43
0
2
Order By: Relevance
“…Monolayers of 1.2 cm 2 exposed surface area were mounted in a horizontal Ussing chamber between 0 and 3 days after the electrical resistance reached a maximum value (800 -1200 ohms) as previously described (27). To create a favorable electrochemical gradient for Cl Ϫ secretion, the basolateral side of the monolayer was bathed in HEPES-buffered KrebsHensleit solution, and the apical was bathed in a low Cl Ϫ solution (125 mM sodium gluconate, 15 mM NaCl, 5 mM KCl, 2 mM CaCl 2 , 1 mM MgCl 2 , 10 mM HEPES, pH 7.4, 280 -290 mOsmol).…”
Section: Methodsmentioning
confidence: 99%
“…Monolayers of 1.2 cm 2 exposed surface area were mounted in a horizontal Ussing chamber between 0 and 3 days after the electrical resistance reached a maximum value (800 -1200 ohms) as previously described (27). To create a favorable electrochemical gradient for Cl Ϫ secretion, the basolateral side of the monolayer was bathed in HEPES-buffered KrebsHensleit solution, and the apical was bathed in a low Cl Ϫ solution (125 mM sodium gluconate, 15 mM NaCl, 5 mM KCl, 2 mM CaCl 2 , 1 mM MgCl 2 , 10 mM HEPES, pH 7.4, 280 -290 mOsmol).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that in some acute clinical situations, the additional benefit of the use of high doses of glucocorticoids is due to their non-genomic effects [113]. The non-genomic effects of dexamethasone on the ATP-induced Ca 2+ signalling and the Cl − secretion in cultured human bronchial epithelial cell monolayers have been also reported [114]. The rapid non-genomic effects of glucocorticoids on human bronchial epithelia may have important clinical implications in the treatment of airway infections such as rhinitis, asthma, and cystic fibrosis [114].…”
Section: Effects Of Glucocorticoids On the Atp-induced No And Ca 2+ Smentioning
confidence: 95%
“…The non-genomic effects of dexamethasone on the ATP-induced Ca 2+ signalling and the Cl − secretion in cultured human bronchial epithelial cell monolayers have been also reported [114]. The rapid non-genomic effects of glucocorticoids on human bronchial epithelia may have important clinical implications in the treatment of airway infections such as rhinitis, asthma, and cystic fibrosis [114]. A recent study showed the novel non-genomic role of glucocorticoids on NO production in acute myocardial ischemic injury [115].…”
Section: Effects Of Glucocorticoids On the Atp-induced No And Ca 2+ Smentioning
confidence: 99%
“…These rapid effects are mediated by non-genomic pathways and are insensitive to inhibitors of transcription and of protein synthesis (reviewed in Falkenstein [22] and Stellato [86]). Some of these effects do not require GR transduction and are based on alterations of the physicochemical properties of the cell membrane that modify levels of intracellular calcium [94]. Other rapid effects of glucocorticoids involve activation of the GR.…”
Section: Fig 1 Molecular Mechanisms Of Glucocorticoidsmentioning
confidence: 99%